H[znak nieskończoności]-methods in population modelling and control - Anita, Sebastian; Aniculaesei, Hheorge (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with an H?-problem with control constraints for the population dynamics. The biological significance of such a problem is discussed. The necessary and sufficient conditions for the existence of a solution to the suboptimal H?-problem for input-output linear population dynamics with control constraints are established. The last part of this paper contains some considerations about possible applications of H?-methods to cancer cell population modelling and control.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka